Expression of an efficient small molecular weight tumour necrosis factor/lymphotoxin antagonist. - Neve, R; Kissonerghis, M; Clark, J; Feldmann, M; Chernajovsky, Y (1996)
TNF-alpha and lymphotoxin are proinflammatory cytokines that are non-homologous in sequence, have similar homotrimeric structure and they exert their biological activity by aggregating two types of shared cell surface receptors. The natural inhibitors of TNF and lymphotoxin are the shed extracellular domains of the p55 and p75 TNF receptors. However recombinant inhibitors composed of the extracellular domains of p75 or p55 receptors dimerized on IgG backbone have been shown to be much more effective. We have produced a dimeric form of the human p75 TNF receptor extracellular domain based on the structure of the native soluble shed receptor. The dimer was engineered by genetically linking the monomeric forms with a polyglycine-serine linker. Biochemical characterization showed that this dimeric TNF receptor elutes from a TNF affinity column at a lower pH than the monomeric form. Biological assay revealed this novel antagonist to be as efficient as a dimer based on an immunoglobulin backbone. However this new dimer is smaller, stable, and could have greater penetration into tissues.